TRANSFORMASI PENDIDIKAN DIGITAL: INOVASI PEDAGOGI, TANTANGAN SISTEMIK DAN ARAH MASA DEPAN - Nursalam Siradjuddin; Muhammad Efendi Hasibuan; Muhammad Yusuf; Mochamad Nangim; Nilawati Tadjuddin (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
The transformation of digital education has become a strategic issue in the development of educational systems in an era of rapid technological advancement. This study aims to comprehensively examine digital pedagogical innovations, the systemic challenges encountered, and the future directions of digital education based on recent research findings. The research method employed is a qualitative literature review, drawing on national and international peer-reviewed journal articles published within the last five years (2019–2024). Data were analyzed using thematic analysis to identify patterns, trends, and key issues relevant to the research objectives. The results indicate that digital pedagogical innovations, such as blended learning, the use of Learning Management Systems, and learner-centered approaches, play a crucial role in enhancing learning flexibility and student engagement. However, the implementation of digital education continues to face systemic challenges, including disparities in access to technology, limited infrastructure, and insufficient digital competencies among educators. Furthermore, the future direction of digital education is projected to increasingly involve intelligent technologies such as artificial intelligence, adaptive learning, and learning analytics. This study concludes that the successful transformation of digital education requires strong synergy between pedagogical innovation, human resource readiness, and sustainable education policies